2020
DOI: 10.1061/jtepbs.0000438
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Exclusive and Pooled TNC Services in Singapore and the US

Abstract: On-demand mobility services provided by transport network companies (TNCs) have experienced significant growth in their adoption and diversification of services in major metropolitan cities around the world. This study presents analysis of primary data from Singapore, exploring the sociodemographics of TNC users, who (among these TNC users) is more likely to pool their trips, and what modes these services are replacing. We compare these results to a comprehensive literature review of similar studies of TNC use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
5
12
0
Order By: Relevance
“…Screening responses according to these filters resulted in the removal of 1,008 invalid responses and produced a dataset of 4,365 responses. While this process resulted in the removal of a high number of screened responses (;23%), this level is similar to other online surveys of TNC users (3,10).…”
Section: Data Cleaning and Weightingsupporting
confidence: 78%
See 2 more Smart Citations
“…Screening responses according to these filters resulted in the removal of 1,008 invalid responses and produced a dataset of 4,365 responses. While this process resulted in the removal of a high number of screened responses (;23%), this level is similar to other online surveys of TNC users (3,10).…”
Section: Data Cleaning and Weightingsupporting
confidence: 78%
“…In relation to driving, Rayle et al (8) and Schaller (5) found that non-car owners are overrepresented among TNC users. Broadly speaking, many studies find TNC users are younger, better educated, higher-income individuals (1,3,9). In this camp, Kooti et al (10) found that higher-income riders not only take more rides but are also more likely to take private ridehailing trips.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Comparte trips, on the other hand, are most likely to be replaced by public transport (25%) than by private car (11%) or taxi (9%). The finding that exclusive ridehailing trips are more likely to replace private, motorized modes while pooled ridehailing trips are more likely to replace public transport is similar to results seen in Singapore despite its different urban and transportation context (3).…”
Section: Travel Behavior Of Ridehailing Userssupporting
confidence: 66%
“…Ridehailing trips in the U.S.A. appear to be replacing public transport, walking and bicycling more than personal vehicle use on a trip-by-trip basis, but access to ridehailing can also help support more multimodal lifestyles that do not rely on owning and using a car, potentially encouraging use of public transport and other non-motorized travel ( 2 ). Fewer studies consider the differential adoption of exclusive and pooled ridehailing services, with mixed results across most sociodemographic groups ( 3 ).…”
Section: Literature Reviewmentioning
confidence: 99%